Exploring zakat payers’ attitudes determinants on trust in zakat institutions - ., Zulfikri; Kassim, Salina; Othman, Anwar Hasan Abdullah (IIUM Press, 2023)
This study aimed to explore the zakat payers’ determinants on intention to trust zakat institutions. Grounded in a qualitative research design, this study utilized an extensive literature review to analyse relevant research and identify the factors that influence the phenomenon under analysis. Drawing upon the Theory of Planned Behaviour, a framework is proposed to explain these factors. The research found that zakat payers’ attitude determinants influencing trust in zakat institutions is primarily influenced by their perception of the institution’s reputation, satisfaction with zakat distribution, service quality, and disclosure practices.